International macroeconomics - Makin, A. J.; Makin, A. J. (Harlow : Financial Times Prentice Hall, 2002)
This book presents the core theoretical frameworks of international macroeconomics to explain the significance and behaviour of exchange rates, international competitiveness, interest rates, capital flows, current account balances, foreign investment, foreign debt and economic growth in open economies.
Previous ed. published as: Open economy macroeconomics. Melbourne : Pearson Education, 1996.
Includes bibliographical references and index.
gau 29/01/14, rpm/18/06/15
Loans
Keywords: Macroeconomics